1997
DOI: 10.1118/1.598019
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a diode array for enhanced dynamic wedge dosimetry

Abstract: The performance of a diode array (Profiler) was evaluated by comparing its enhanced dynamic wedge (EDW) profiles measured at various depths with point measurements using a 0.03 cm3 ionization chamber on a commercial linear accelerator. The Profiler, which covers a 22.5 cm width, was used to measure larger field widths by concatenating three data sets into a larger field. An innovative wide-field calibration technique developed by the manufacturer of the device was used to calibrate the individual diode sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…5 The dead time measurements were carried out using 4 MV x rays over the range of the dose rates ͑250, 200, 150, and 100 MU/min͒ available with the commercial medical linear accelerator. The measured dead times were 0.7Ϯ1.1 ms at the dose rate of 250 MU/min, 0.8Ϯ1.7 ms at 200 MU/min, 1.9 Ϯ2.2 ms at 150 MU/min, and 0.4Ϯ2.3 ms at 100 MU/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The dead time measurements were carried out using 4 MV x rays over the range of the dose rates ͑250, 200, 150, and 100 MU/min͒ available with the commercial medical linear accelerator. The measured dead times were 0.7Ϯ1.1 ms at the dose rate of 250 MU/min, 0.8Ϯ1.7 ms at 200 MU/min, 1.9 Ϯ2.2 ms at 150 MU/min, and 0.4Ϯ2.3 ms at 100 MU/min.…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to verify the dose distribution before an IMRT treatment procedure is applied to a patient. Some methods to verify the delivered dose have been investigated by Zhu et al 5 using a diode array, Ibbott et al 6 using magnetic resonance imaging of BANG polymer gel dosimeters, Curtin-Savard and Podgorsak using a commercial electronic portal imaging device to evaluate the segmented beam delivery, 7 and Ma et al using an accurate and independent Monte Carlo dose calculation algorithm. 8 However, except for the independent dose calculation method, the experimental techniques require a lengthy and sometimes costly analysis process before the data is available.…”
Section: Introductionmentioning
confidence: 99%
“…These have been verified by many researchers, and these dose evaluation methods are still in use today. 11,[27][28][29][30][31][32][33][34] In addition, the evaluation of an absolute isocenter dose and 2D dose distribution are considered to be adequate for delivery QA of arc therapy, such as IMAT or VMAT. 35,36 Wagner and Vorwerk 35 reported that the use of a 2D ionization chamber (MatriXX™; IBA Dosimetry GmbH, Schwarzenbruck, Germany) for VMAT plan verification is reasonable in clinical routine use.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have used different dosimetric methods to measure dose distribution for the dynamic wedge. For example diode detector arrays, radiation sensitive film, Fricke gel dosimeters and ion chamber arrays (Bengtsson et al 1996and Zhu et al 1997.…”
Section: Simple Ldr Brachytherapymentioning
confidence: 99%